ON THE STUDY OF SPELLING RULES AT SECONDARY SCHOOL: HISTORY AND MODERNITY - Lyudmila G. Larionova (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2021)
The article is devoted to the main problems of studying the rules of Russian spelling at secondary school at different stages of its development. It is presented a general overview of scientific and methodological works, from the 19th century to the present day, which consider the history of formation, streamlining of methodological thought in the study of spelling rules, determining their significance for the formation of literate writing of students. In addition, in the process of research, problems are raised: why spelling rules are necessary; if it is possible to teach schoolchildren to write literally without memorizing the wording of spelling rules; if you teach students on the basis of rules, then what should be the requirements for the formulation of spelling rules from a linguistic, methodological and psychological-pedagogical point of view. The author’s analysis of thesis research from 2000 to 2020 made it possible to determine the basic approaches to the study of spelling rules in a modern secondary general education school: the communicative-activity approach, the cognitive-activity approach, the programmed approach (or programmed teaching) - and to identify the linguodidactic principles underlying the study of spelling rules within each of these approaches. In the course of the study, special attention was paid to the analysis of the spelling course in the new educational-methodical complex (EMC) in the Russian language (authors: M.M. Razumovskaya, S.I. Lvova, V.I. Kapinos, V.V. Lvov). It is concluded that the study of spelling rules (and this has been proven by leading scientists-methodologists of the past and present times) form the basis of the school spelling course, which is therefore called rule-oriented. Learning spelling is impossible without rules and dictionaries. The formation of the relative literacy of students, which is formed in secondary school, requires time, observance of stages and reliance on spelling rules studied as educational and scientific texts of linguistic content, taking into account the development of all types of speech activity in unity and interconnection. Each lesson of the Russian language, in which the spelling rule is studied, is a lesson in the development of students’ speech, where their literacy is formed in the broad sense of the word.